1974
DOI: 10.1128/iai.9.2.286-293.1974
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Administered in the Cerebrospinal Space and Its Effect on Rabies in Rabbits

Abstract: Because combined administration of intramuscular and intravenous interferon has been partially successful in the incubationary treatment of rabies, the effect of direct interferon administration into the cerebrospinal fluid space was tested. After injecting 1,800 U of interferon into the cisterna magna or the lateral ventricle, periodic samples, obtained by cisternal taps, showed that 1 to 5% remained after 24 h, as opposed to the known clearance of interferon from the bloodstream to this level within minutes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Subsequent samples of CSF showed the presence of interferon, indicating that following an intrathecal injection it remained present in CSF for at least 24 hours. This finding has been noted in animal work (Ho et al 1974, Habif et af. 1975, Hilfenhaus ef al.…”
Section: Discussionsupporting
confidence: 80%
“…Subsequent samples of CSF showed the presence of interferon, indicating that following an intrathecal injection it remained present in CSF for at least 24 hours. This finding has been noted in animal work (Ho et al 1974, Habif et af. 1975, Hilfenhaus ef al.…”
Section: Discussionsupporting
confidence: 80%
“…inject interferon either intramuscularly or intravenously, and then analyze for interferon in cerebrospinal fluid. The animals tested include mice, hamsters, rabbits, monkeys and humans; the sites of injections include cerebrum, theca vertebralis, cisterna magna, lateral ventricle, directly into the cerebrospinal fluid, and lumbar-spinal; inducers include poly(rI).poly(rC), blue tongue virus, rabies virus, and Sendai virus (Kono and Ho, 1965;Ho and Ke, 1970;Cathala and Baron, 1970;Jameson et al, 1977;Stewart II and Sulkin, 1966;Allen and Cochran, 1972;Ho et al, 1974;Habif et al, 1975;Hilfenhaus et al, 1977b). The overwhelming agreement among all the studies reported was encouraging.…”
Section: Clearance From the Cerebrospinal Fluid: The Blood-brain Barrmentioning
confidence: 99%